Organisational Culture and Dynamics (Global Journal of Management and Business Research, 2018)
Every organisation has something unique about the way it operates. It is that uniqueness that every other organisation uses as a mark of distinction in describing that organisation. The ways an organisation operates vis a vis, its beliefs, values and assumptions is what I have conceptualized as organisational culture. The culture of an organisation, to a very large extent, determines the performance of the individuals that work in that organisation and by extension, the organisational performance. This paper takes an in-depth review of the relationships between some organisational culture parameters and individual performance, organisational performance and sustainability. From the extant literature, it till stand to reason that organisations should focus on that aspects of their cultures that are positive in outlook and yield the greatest positive result in terms of organisational outcomes. On the other hand, they should do away with those aspects of their culture, which are not adding any value to their bottom-line. This study totally supports the evidence that managing your organisational culture effectively will lead to a higher organisational performance.
Keywords: organisational culture; organizational outcomes; strong organisational culture; weak organisational culture